Outcome Mapping as a Monitoring and Evaluation Tool for Livestock Value Chain Interventions: The Case of imGoats - Hailemichael Taye Beyene; Kees Swaans; Birgit Boogaard; Ramkumar Bendapudi; Saskia Hendrickx (Journal of MultiDisciplinary Evaluation)
Background: The dynamic and complex natures of value chains added up with the multi-layered and open socio-technical systems that are affected by a range of factors and the continuous adaptation processes to changing conditions, makes measuring changes of value chain interventions a challenging task. Selection of M&E approach is dictated by the reality of multiple actors, relationships and perspectives in complex change processes. The traditional M&E approaches and tools specifically the log frame have been criticized for its failure in measuring changes in complex interventions. M&E approaches and tools that are learning focused, flexible, allow involvement of stakeholders, capture unintended results and focus on contribution of the interventions are more appropriate.